Differential game theory with FPA optimization in multi-area power system - S. Khadarvali; V. Madhusudhan; R. Kiranmayi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
The distribution generation penetration increases due to the increased need of power. These penetration causes problem of frequency deviations. In this paper the in multi-area power system the combination of renewable energy resources is proposed. Here the area 1 & area 2 are thermal power plant. Hydro power generation plant is taken in area-3 & area-4. Renewable energy system is considered in area-5. Here the cyber security attack is taken as change in power in the entire area. This can make the power block out or wrong data entry. Here differential game theory-based problem formulation is done. The PI controller and differential game theory with flower pollination are compared for performance of fast response. The MATLAB 2017b is used for building the areas and algorithm